2020
DOI: 10.1017/pasa.2020.6
|View full text |Cite
|
Sign up to set email alerts
|

The GLEAMing of the first supermassive black holes

Abstract: We present the results of a new selection technique to identify powerful ( $L_{\rm 500\,MHz} \gt 10^{27}\,\text{WHz}^{-1}$ ) radio galaxies towards the end of the Epoch of Reionisation. Our method is based on the selection of bright radio sources showing radio spectral curvature at the lowest frequency ( ${\sim}100\,\text{MHz}$ ) combined with the traditional faintness in K-band for high-redshift galaxies. This technique is only possible, thanks to the Galact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 69 publications
6
13
0
Order By: Relevance
“…Nevertheless, we expect that upcoming and ongoing wide-area surveys such as RACS and the development of dedicated selection techniques in the radio band (e.g. Drouart et al 2020) will find many more radio-powerful sources at z > 6 (e.g. Amarantidis et al 2019).…”
Section: Radio Loudness and Comparison With High-z Rl Qsosmentioning
confidence: 99%
“…Nevertheless, we expect that upcoming and ongoing wide-area surveys such as RACS and the development of dedicated selection techniques in the radio band (e.g. Drouart et al 2020) will find many more radio-powerful sources at z > 6 (e.g. Amarantidis et al 2019).…”
Section: Radio Loudness and Comparison With High-z Rl Qsosmentioning
confidence: 99%
“…3; Drouart et al 2020). While the observed 1.4 GHz flux density of COS-87259 is ≈1000× fainter than that of most currently known 𝑧 > 4 radio galaxies (Saxena et al 2018;Drouart et al 2020;Yamashita et al 2020), this can be explained by the fact that 𝑧 > 4 radio galaxies are often identified from all-sky surveys that probe much higher radio luminosities relative to the extremely deep VLA-COSMOS data. There are many radio galaxies at lower redshifts (𝑧 < 4) with rest-frame 1.4 GHz luminosities comparable to that of COS-87259 (L 1.4GHz ∼ 10 25.5 W Hz −1 ; e.g.…”
Section: Physical Interpretation Of the Multi-wavelength Sedmentioning
confidence: 91%
“…Ker et al 2012;Saxena et al 2018;Yamashita et al 2020). As an example, we show the radio SED of GLEAM 0856 at 𝑧 = 5.55 in the inset panel which shows an ultra-steep (𝛼 = −1.51) radio slope at 1.4 GHz yet a relatively flat slope (𝛼 = −0.78) at 1 GHz (Drouart et al 2020).…”
Section: Flux Density [µJy]mentioning
confidence: 98%
See 2 more Smart Citations